Potensi Bacillus licheniformis dan Streptomyces olivaceoviridis sebagai Penghambat Pertumbuhan Jamur Saprolegnia sp. Penyebab Saprolegniasis pada Ikan secara In Vitro [Potential of Bacillus licheniformis and Streptomyces olivaceoviridis as Inhibiting The Growth of Fungus Saprolegnia sp, Cause Saprolegniasis on Fish by Using In Vitro] - Oktantia Frenny Anggani; Rahayu Kusdarwati; Hari Suprapto (Jurnal Ilmiah Perikanan dan Kelautan, 2015)
Abstract Saprolegniasis is a fungal disease on fish caused by Saprolegnia sp, which is saprophyte, damaging healthy tissue and makes the immune system in fish deacreased. The uniquennes of Saprolegnia sp has the main components of the cell wall in the form of chitin that was instrumental in shaping the structure of the tip growth of fungal hyphae. Control of fungal pathogenic Saprolegnia sp can use chitinolytic microorganisms based on ability to produce chitinase for example using bacteria. This study aims to potential of Bacillus licheniformis and Streptomyces olivaceoviridis as inhibiting the growth of fungus Saprolegnia sp, cause saprolegniasis on fish by using in vitro. The research method is experimental with completely randomized design (CRD), which consists of four treatments with five replications. The experimental used is A (Saprolegnia sp and Bacillus licheniformis), B (Saprolegnia sp and Streptomyces olivaceoviridis), C negative control (Saprolegnia sp) and D positive control (Saprolegnia sp and Ketokonazol 2 %). The main parameters measured were observed inhibition zone on each treatment. Supporting parameters were observed is an observation of abnormal hpyphae structure after being induced by bacteria Bacillus licheniformis dan Streptomyces olivaceoviridis. Data were analyzed using analysis of variants (ANOVA) and to know the difference between treatments were determined by Tukey honestly significant difference (Tukey HSD) Test. The results showed that the potential of chitinolytic Bacillus licheniformis can provide a good barrier of 4,62 cm by 5,48 cm compared Streptomyces olivaceoviridis in inhibiting the growth Saprolegnia sp. Suggestions in this research is the need to further research on the value of chitinase Bacillus licheniformis and Streptomyces olivaceoviridis. Further research by using in vivo.